(untitled) (Socio-economic relations in the digital society, 2019)
The article includes the studies of the structure and typology of the most stable banking systems of particular countries and systems of banking supervision. The primary factors of banking system stubility are revealed. The strategic ways to ensure the stability of the banking system of Ukraine are suggested. The research contains the list of main characteristic of a stable banking system: absence of bank failures; profi tability; compliance with national legislation; performance of its functions in the usual terms and the conditions of the external shocks or strengthening of the imbalances with possible transformation according to the challenges of the time; Directions to stabilize the banking system of Ukraine, which are based on the practices of the most stable banking systems, in particular by strengthening the role of the NBU in banking regulation, are determinate.